Outside Front Cover: Biotechnology Journal 3/2020. Issue 3 (2nd March 2020) - Kim, Youna; Park, Yeonkyung; Lee, Chang Yeol; Park, Hyun Gyu
Abstract : A label‐free and enzyme‐free uracil DNA glycosylase (UDG) activity assay is described. In the upper left bubble, detection duplex probe serving as substrate for UDG releases a catalyst strand (blue strand) due to the UDG‐catalyzed degradation of uracil, which subsequently promotes the toehold‐mediated strand displacement (TMSD) reaction in the upper right bubble. As a result, active split G‐quadruplexes are produced leading to the colorimetric response in the bottom bubble. This is reported by Youna Kim, Yeonkyung Park, Chang Yeol Lee, Hyun Gyu Park in article 1900420 .